1995
DOI: 10.3354/meps126177
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the relative utilization of dietary protein for energy and biosynthesis by the mussel Mytilus edulis

Abstract: Mussels Mytilus edulis were collected from Whitsand Bay in southwest England during Apnl, July and September 1993 and January 1994, and fed a defined diet of prekilled microalgae with one of 2 types of mixed protein/carbohydrate microcapsules. Both capsule types were comprised of the same w/w proportion of "N-labeled protein and nonlabeled carbohydrate. However, Types 1 and 2 contained trace amounts of ["Clcarbohydrate and [14C]protein, respectively. Defecation, excretion, respirdtion and incorporation of I4C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 14 publications
3
13
0
2
Order By: Relevance
“…These results suggest that the adults may have initiated their gonadal development. This conforms with other studies where accumulations of proteins in bivalve tissue are simultaneously an indicator to maturation of gonads (Devi et al 1985;Kreeger 1993;Rivonker and Parulekar 1995), and as a reserve prior to spawning activity (Nagabhushnam and Mane 1978;Gabbott and Peek 1991). Proteins and lipids were continuously metabolised to support energy demand whenever needed (food scarcity or insufficient carbohydrates).…”
Section: Effect Of Dietary Contents Of the Diets On Growth Performancesupporting
confidence: 90%
“…These results suggest that the adults may have initiated their gonadal development. This conforms with other studies where accumulations of proteins in bivalve tissue are simultaneously an indicator to maturation of gonads (Devi et al 1985;Kreeger 1993;Rivonker and Parulekar 1995), and as a reserve prior to spawning activity (Nagabhushnam and Mane 1978;Gabbott and Peek 1991). Proteins and lipids were continuously metabolised to support energy demand whenever needed (food scarcity or insufficient carbohydrates).…”
Section: Effect Of Dietary Contents Of the Diets On Growth Performancesupporting
confidence: 90%
“…Others have also been able to correlate respiration rate with gametogenic cycle ( R a and Kreeger et al (1995) reported ammonium excretion rates comparable to those we found, with high values in periods when glycogen reserves were depleted. Kuenzler (1961) reported an average phosphate excretion rate of 0.086 pm01 P-PO, g-' h-' for Modiolus demissus, while for Mytilus edulis, Kautsky & Wallentinus (1980) reported rates from 0.01 to 0.77 pm01 g-' h-' in February and August, and Asmus et al (1994) measured phosphate excretion rates in mussels ranging from 0.07 pm01 g-' h-' in September to 0.17 pm01 g-' h-' in May.…”
Section: Discussionsupporting
confidence: 73%
“…They concluded that energy or carbon-based SFG overestimated growth under nitrogen-limited conditions. Kreeger et al (1995) demonstrated excretion of the carbon fraction of amino acids which were hydrolysed and transaminated for biosynthesis of proteins, and suggested that mussels were more likely to have been nutritionally limited by their quantitative amino-N requirements rather than by their energy demand. In our study, seasonal NGE for P was always positive and, on average, was higher than for N. However, possible underestimation of P excretion in winter might account for the high NGE for P. A high NGE indicates that a relatively small fraction of the absorbed material is used for maintenance, and a relatively large fraction is available for growth and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…g . Winter 1973, Navarro & Winter 1982, Bayne et al 1987, 1988, 1993, Hawkins & Bayne 1992, Stenton-Dozey & Brown 1992, Willows 1992, Navarro et al 1994, Kreeger et al 1995. Earlier contradictions to the theory of 'physiological control' or 'regulation of filtration rate' have in particular been advanced by Jsrgensen (1990) Riisgdrd et al (1994) note (Jsrgensen 1996)-which gives a comprehensive review of the most recent literature.…”
Section: Discussionmentioning
confidence: 99%